I. Barreñada (Coord.) (2018). Entre España y Palestina. Revisión crítica de unas relaciones. Madrid: Bellaterra. 327 pp. - Gutiérrez de Terán Gómez-Benita, Ignacio (Estudios de Asia y África, 2020)
I. Barreñada (Coord.) (2018). Entre España y Palestina. Revisión crítica de unas relaciones. Madrid: Bellaterra. 327 pp.